FLIPPED CLASSROOM : THE NOVEL LEARNING ENVIRONMENT FOR MEDICAL STUDENTS: FLIPPED CLASSROOM : THE NOVEL LEARNING ENVIRONMENT FOR MEDICAL STUDENTS - Pejin, Irina; Oroz, Sara; Milojkovic, Djordje; Milic, Nikola; Rajović, Nina (Medicinski podmladak, 2022)
Introduction: The ongoing COVID-19 pandemic has strongly initiated digital developments and closed in-person classes in higher education. In order to achieve remote high-quality online delivery, the flipped classroom method has been introduced to both students and teachers. The flipped classroom represents a type of blended learning aiming to increase students’ engagement by preparing materials for learning at home and having face-to-face problem-solving during class time. Aim: To assess attitudes and perceptions of medical undergraduate students toward flipped classroom method of learning. Materials and methods: The cross-sectional study was conducted using online questionnaire distributed among undergraduate medical students attending the Faculty of Medicine University of Belgrade during January 2022. The questionnaire used in this study consisted of 34 questions and was divided among six main sections: demographics, overall attitudes, communication, independence in learning, preparedness and motivation, and creative thinking and collaborative work. Results: A total of 60 students attending the Faculty of Medicine University of Belgrade were included in the study. More than half of the students were female (75,0%) and the mean age was 23,48±1,53 years. Most of the respondents were fifth- and sixth-year students. The results of this study revealed that there are significant differences in students’ perceptions toward flipped classroom method of learning between gender and age group. Female and younger students had more positive attitudes toward flipped classroom than male and older students. Conclusion: Flipped classroom method of learning suits the demands of medical students at a university level, developing their problem-solving skills and higher-order thinking. Bearing in mind that younger students had positive perceptions and attitudes toward flipped classroom method of learning, curriculum designers and educators should adjust the lessons and teaching methods strategies to students’ preferences in order to help them to gain their full academic potential.